Design Method for Specific Charge in Deep Mining considering Influence of In Situ Stress - Fengpeng Zhang; Qiqi Hao; Xiulong Wang; Zhaoguo Qiu (Advances in Civil Engineering)
In situ stress has a large influence on blasts in deep mines and should be considered in blasting design. In this study, explosion crater tests were conducted to investigate the variation of specific charges under different stress loading conditions. It was revealed that rock blasting under high stress is different from that under low stress. A correction coefficient for specific charge was defined to consider the influence of in situ stress on blasting. A quantitative relation between the correction coefficient, stress-to-strength ratio, and lateral stress coefficient was presented. Based on the explosion-crater test results, a design method for specific charges was proposed with the consideration of in situ stress. Finally, the design method was applied to a field blasting test at Hongtoushan Copper Mine. The test results indicate that the proposed design method can effectively use the high in situ stress at depth for rock fragmentation. Compared with the original blasting design, the specific charge is reduced by 19.8% and the average block rate is reduced from 6.8% to 2.84%. At the same time, the blasting boundary is well controlled and the ore loss and dilution rates are reduced. This research has important guiding significance to deep mine blasting design.